Hedge fund market wizards : how winning traders win - Schwager, Jack D., 1948- (Wiley, 2012)
"Hedge Fund Market Wizards will be a modern day sequel to the highly successful Market Wizards and New Market Wizards written over 20 years ago. These two earlier volumes have become classics in the investment literature and have been read by virtually every hedge fund manager, as well as by a much broader lay audience. This new volume in the series will follow the same effective formula used by its predecessors. The book will devote a chapter to each of a broad array of highly successful traders, ranging widely in the markets they trade and their methodologies, but sharing in their achievement of superior performance. Each chapter, following the original format, will include an introductory section, a core section based on an interview with the trader, and a conclusion section that seeks to draw useful trading and investment lessons illustrated by the trader's approach and advice"--